Sistem Informasi Penjualan Berbasis Website Dengan Algoritma Apriori Pada PT. Mitra Abdi Setia Bekasi - Ardilla , Marni; Hartanti , Dian; Hantoro , Kusdarnowo (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2023)
Printing is a need that is currently widely used in various fields, this is because printing helps a lot in the promotion process or efforts to introduce a product to a new business. Printing at PT. Mitra Abdi Setia currently does not have a sales information system so the research wants to analyze the ordering system that will be run at PT. Mitra Abdi Setia and designed a new website-based system in order to provide convenience in ordering online. A priori algioritma is the best know algorithm for finding high-frequency patterns. Association rule mining analysis is a data mining technique to find the rules of a combination of items. One of the stages of association analysis that attracts the attention of many researchers to produce efficient algorithms is the analysis of high-frequency patterns (frequent pattern mining). The purpose of this study is to build a website and be able to mine data that will later produce best-selling sales data information, and consumers will know the recommended products from PT. Mitra Abdi Setia.